(untitled) (Universal International Scientific Journal, 2026)
The article is devoted to the formation and development of communicative competence of schoolchildren in the process of learning the Russian language, developing the student’s cognitive abilities through enriching vocabulary, correctly connecting words, using them in speech, logically and methodologically subordinating the use of various grammatical means, consistently expressing one’s thoughts, and subordinating the means of statement, text, and expression to the main idea.